Prevalence of Anemia and Risk Factors of Anemia in Pregnant Women: A Cross-Sectional : Study at Saritani Community Health Center, Boalemo - Siti Indrayani; Rani Safitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia in pregnant women is a public health problem that remains high in Indonesia and impacts maternal health and fetal development. This study aims to determine the prevalence of anemia and risk factors in pregnant women at the Saritani Community Health Center, Boalemo. The study used a cross-sectional design on 28 pregnant women selected by purposive sampling. Data were collected through interviews using a structured questionnaire and hemoglobin level examination (HemoCue). Descriptive and bivariate analyses using the Chi-Square test were performed, with p < 0.05 as the significance limit. The results showed a prevalence of anemia of 42.9 % . Factors significantly associated with anemia included education level (p = 0.041), adherence to Fe tablet consumption (p = 0.022), parity (p = 0.037), and pregnancy spacing (p = 0.049). Mothers with low education, non-adherence to Fe tablet consumption, high parity, or pregnancy spacing <2 years had a higher risk of developing anemia. Age and diet did not show a significant association.